THE OFFICIAL POSITION OF UKRAINE TOWARDS THE EURASIAN CUSTOMS UNION 2010 - 2013: A FAILED ATTEMPT TO MOVE FROM THE OLD NEIGHBOURHOOD? - Yakovenko, K. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The following article is summarizing and analysing the official position of Ukrainian president Victor Yanukovych and the top Ukrainian oligarchs regarding the possibility of membership in the Eurasian Customs Union, focusing on the timeframe of the years 2010-2013. The author claims that Ukraine’s president in office and most successful entrepreneurs supported the eurointegration course; thus, just before the third Eastern Partnership Summit in Vilnius, the perspective of signing the Deep and Comprehensive Free Trade Agreement with the European Union prevailed over the opportunity to enter the Eurasian Customs Union with Russia, Belarus and Kazakhstan.